2011
DOI: 10.3810/pgm.2011.11.2495
|View full text |Cite
|
Sign up to set email alerts
|

Review: A Single-Pill Combination of Telmisartan plus Amlodipine for the Treatment of Hypertension

Abstract: Despite an increased proportion of patients with hypertension achieving recommended blood pressure (BP) targets, BP control remains suboptimal in many patients. A range of combination therapies utilizing medications with differing mechanisms of action have been shown to provide superior BP-lowering efficacy than monotherapy with individual components. Single-pill combinations deliver improved convenience and may help to improve patient compliance. A single-pill combination of the angiotensin receptor blocker (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Among the subgroup of 385 patients taking 40/10/12.5 mg of O/A/H containing 10 mg of amlodipine, six patients (1.5%) experienced edema due to O/A/H administration. In comparison, a previous study by Guthrie reported a significantly higher edema incidence of 10.8% in a subset using an SPC of telmisartan and amlodipine 10 mg [30]. The lower edema incidence observed in the present study is likely due to the exclusion of patients who had previously experienced edema while using CCB before switching to O/A/H.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Among the subgroup of 385 patients taking 40/10/12.5 mg of O/A/H containing 10 mg of amlodipine, six patients (1.5%) experienced edema due to O/A/H administration. In comparison, a previous study by Guthrie reported a significantly higher edema incidence of 10.8% in a subset using an SPC of telmisartan and amlodipine 10 mg [30]. The lower edema incidence observed in the present study is likely due to the exclusion of patients who had previously experienced edema while using CCB before switching to O/A/H.…”
Section: Discussioncontrasting
confidence: 91%
“…As previously mentioned, the target BP values in such patients are set lower than in those without concomitant risks. Although the more aggressive approach to antihypertensive treatment in patients with additional cardiovascular risk factors might theoretically lead to higher frequency of side effects associated with hypotension, the hypotension rate in the present study (1.51%) was within the range reported in previous studies on patients with similar characteristics (0.6–2.4%) [ 12 14 , 16 , 17 , 30 ]. An extension study of the TRINITY trial also showed that ADRs occurring in patients with additional cardiovascular risk were consistent with the established safety profile of O/A/H [ 15 ].…”
Section: Discussionsupporting
confidence: 77%
“…SPCs of telmisartan or hydrochlorothiazide have greater efficiency than monotherapy in all stages of hypertension [16]. Importantly, SPCs use resulted in fewer adverse effects, such as edema and hypokalemia, compared with amlodipine and hydrochlorothiazide monotherapy [16,17].…”
Section: Telmisartan As a Combination Therapymentioning
confidence: 99%
“…Similarly, an SPC of telmisartan and amlodipine, including all doses, provides superior BP reduction than other antihypertensive agents alone and demonstrates 24-hour BP control [17]. Indeed, telmisartan plus amlodipine might be a reasonable choice for hypertensive patients who likely will require more than one agent for BP control [17]. Furthermore, the use of SPC offers better patient adherence in comparison to a separate agent [17].…”
Section: Telmisartan As a Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation